2004
DOI: 10.1023/b:card.0000025751.82774.a9
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil Protects Against Lethal Ischemic Ventricular Arrhythmias and Up-regulates Endothelial Nitric Oxide Synthase Expression and Sulfonylurea Receptor 2 mRNA in Conscious Rats with Acute Myocardial Infarction

Abstract: Nicorandil is an adenosine triphosphate sensitive K (K-ATP) channel opener and a nitric oxide donor. K-ATP channels and nitric oxide are important factors in ischemic preconditioning, which in turn suppresses reperfusion arrhythmias. The present study sought to evaluate whether nicorandil suppresses ischemic-induced ventricular arrhythmias and enhances sulfonylurea receptors (SUR 2; subunit of K-ATP channel), endothelial nitric oxide (eNOS), and inducible nitric oxide (iNOS) expression in the left ventricle af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…As mentioned previously, nicorandil contains a nitrate moiety in its chemical structure, allowing it to function as a NO donor. On the other hand, other investigations [56,57] showed that nicorandil is able to upregulate eNOS expression and increase NO release following ischemia. Thus, it seems that upregulation of eNOS, which leads to acute production of NO, in addition to the NO donor property of nicorandil and the nicotinamide moiety that makes it a potent hydroxyl radical scavenger, is partially or totally responsible for its beneficial effects in remission of IBD.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned previously, nicorandil contains a nitrate moiety in its chemical structure, allowing it to function as a NO donor. On the other hand, other investigations [56,57] showed that nicorandil is able to upregulate eNOS expression and increase NO release following ischemia. Thus, it seems that upregulation of eNOS, which leads to acute production of NO, in addition to the NO donor property of nicorandil and the nicotinamide moiety that makes it a potent hydroxyl radical scavenger, is partially or totally responsible for its beneficial effects in remission of IBD.…”
Section: Discussionmentioning
confidence: 96%
“…Although doses of nicorandil and cromakalim used in the current study were higher than previous study in dogs they failed to shorten QT interval in the anesthetized rabbits. This is may be due to the differences in pharmacokinetics and pharmacodynamics of drugs in different animal species (D'Alonzo et al, 1994a(D'Alonzo et al, , 1994bHorinaka et al, 2004). The finding of the current study showed that pinacidil induced VF in about 20% of the anesthetized rabbits.…”
Section: Discussionmentioning
confidence: 50%
“…In the ischemic myocardium, nicorandil has revealed cardioprotective effects. This is demonstrated by reduced myocardial necrosis and improved myocardial stunning [22] following administration. Angina pectoris is brought about by transient episodes of myocardial ischemia which create an imbalance in the myocardial oxygen supply and demand relationship.…”
Section: Nicorandilmentioning
confidence: 92%
“…Both mechanisms of its action contribute to vasodilation, but are independent. At lower concentrations, nicorandil activates the K ATP channel, while at higher concentrations, it acts through NO donation [21,22]. Nicorandil brings about sustained vasodilation, it markedly relaxes coronary vascular smooth muscle and increases the coronary blood flow.…”
Section: Nicorandilmentioning
confidence: 99%